2022
DOI: 10.3390/molecules27165104
|View full text |Cite
|
Sign up to set email alerts
|

Z-Guggulsterone Is a Potential Lead Molecule of Dawa-ul-Kurkum against Hepatocellular Carcinoma

Abstract: An ancient saffron-based polyherbal formulation, Dawa-ul-Kurkum (DuK), has been used to treat liver ailments and other diseases and was recently evaluated for its anticancer potential against hepatocellular carcinoma (HCC) by our research team. To gain further insight into the lead molecule of DuK, we selected ten active constituents belonging to its seven herbal constituents (crocin, crocetin, safranal, jatamansone, isovaleric acid, cinnamaldehyde, coumaric acid, citral, guggulsterone and dehydrocostus lacton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Bioactive compounds have several action mechanisms involved in the induction of cancer cell apoptosis. In tumor cells, they function via modulating the extrinsic and intrinsic pathways of apoptosis, channeling important cell signaling pathways such as mTOR-AKT, Ras/NF-κβ, ROS/JNK, JAK/STAT, and Src/Fak and regulating gene expression ( Huang et al, 2018 ; Gupta et al, 2021 ; Gupta et al, 2022a ; Gupta et al, 2022b ; Gupta et al, 2023 ). Treatment with Guggulsterone also altered the expression of different gene families which collaborate in the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive compounds have several action mechanisms involved in the induction of cancer cell apoptosis. In tumor cells, they function via modulating the extrinsic and intrinsic pathways of apoptosis, channeling important cell signaling pathways such as mTOR-AKT, Ras/NF-κβ, ROS/JNK, JAK/STAT, and Src/Fak and regulating gene expression ( Huang et al, 2018 ; Gupta et al, 2021 ; Gupta et al, 2022a ; Gupta et al, 2022b ; Gupta et al, 2023 ). Treatment with Guggulsterone also altered the expression of different gene families which collaborate in the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is most commonly seen chronic liver disease caused by alcohol overuse, hepatitis B/C virus (HBV/HCV), or metabolic syndrome [22]. It is frequently multi-nodular when detected because of its synchronous progression.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, saffron is mainly used for treating cardiovascular diseases and liver diseases in clinics. At present, there are many preparations containing saffron (Figure 1), such as Dawa UL kurkum [14], llkl [15], saffron total glycoside tablets [16], and Liuwei xihonghua koufuye, Bawei xihonghua Qingganre capsules, which are widely used in liver diseases [17]. Modern studies have found that saffron is a good anti-inflammatory, antioxidant, and anti-apoptotic agent, and has a significant liver protective effect [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%